INNOVATION OF BIOCHEMISTRY LEARNING IN WELCOMING THE SUPER SMART SOCIETY 5.0 ERA - Ratna Kumala Dewi (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
TTechnological developments are now in the era of super-smart society 5.0 which is an advanced solution to the 4.0 industrial revolution. The era of super-smart society 5.0 is a learning innovation that changes from basic literacy to digital literacy. This study aims to analyze the innovation of Biochemistry learning in the Department of Chemistry at UIN Sayyid Ali Rahmatullah Tulungagung in welcoming the era of super-smart society 5.0. The research method used descriptive qualitative. The data analysis technique was carried out using a literature review. The method of data collection was carried out by observation, distributing questionnaires, documentation, lecturer interviews, and student interviews. The research instrument consisted of observation sheets, questionnaires, and interview sheets. The results showed that in the era of super-smart society 5.0, lecturers and students were required to be quick in making decisions and solutions when learning Biochemistry. Lecturers must dig up information and look for innovations so that students can think ahead and keep up with the times according to the era of super-smart society 5.0. Lecturers act as tutors or teachers, facilitators, and inspire students to achieve learning objectives. Based on the results of the study, it can be concluded that lecturers must have the ability in digital literacy and train students to be able to think critically and creatively in learning Biochemistry in the era of super-smart society 5.0.